Local mechanical properties of an ultrastable metallic glass. (22nd May 2020) - Dziuba, Thomas; Luo, Yuansu; Samwer, Konrad
Abstract: Recently, ultrastable glasses gained growing attention due to the revelation of the mechanism leading towards the understanding of glasses and glass transition in general. We report the adaptation of vapor deposition techniques to create ultrastable amorphous phases of Cu50 Zr50 with different mechanical properties. Investigations using atomic force acoustic microscopy reveal a connection between an enhanced elastic modulus, its low potential energy and its homogeneity throughout the sample. Here, higher stability is always accompanied by high homogeneity. We relate the preparation conditions to the resulting mechanical properties, potentially opening a path to systematically engineer ultrastability in metallic glasses. Furthermore, we give a qualitative explanation for our results in the framework of the potential energy landscape, providing insights to the origin of ultrastability in metallic glasses in general.